Mass spectrometry-based identification of S-nitrosocysteine in vivo using organic mercury assisted enrichment - Doulias, Paschalis-Thomas (2012)
Protein S-nitrosylation is considered as one of the molecular mechanisms by which nitric oxide regulates signaling events and protein function. The present review presents an updated method which allows for the site-specific detection of S-nitrosylated proteins in vivo. The method is based on enrichment of S-nitrosylated proteins or peptides using organomercury compounds followed by LC-MS/MS detection. Technical aspects for determining the reaction and binding efficiency of the mercury resin that assists enrichment of S-nitrosylated proteins are presented and discussed. In addition, emphasis is given to the specificity of the method by providing technical details for the generation of four chemically distinct negative controls. Finally it is provided an overview of the key steps for generation and evaluation of mass spectrometry derived data.